Pathological features and their prognostic impacts on oral cavity cancer patients among different subsites – A singe institute’s experience in Taiwan - Liu, Shih-An; Wang, Chen-Chi; Jiang, Rong-San; Lee, Fang-Yi; Lin, Wen-Jiun; Lin, Jin-Ching (Scientific reports, 2017)
We investigated the relationship of different primary subsites together with their pathological features on the survival of oral cavity squamous cell carcinoma (OCSCC) patients. We retrospectively reviewed OCSCC patients and documented their demographic data, pathological features and clinical outcome. The Cox proportional hazard model was used to examine the influence of various pathological features on the prognosis in different subsites of oral cavity. There were totally 1,383 OCSCC patients enrolled for final analysis. Perineural invasion had a poor prognosis at the early stage of OCSCC patients especially those with primary at the tongue. In addition, lymphovascular invasion was associated with poor survival at the late stage especially those with primary at the buccal mucosa and the tongue. The impact of pathological features on the survival of OCSCC patients varied in different subsites. Further investigation is warranted to validate our finding in a multicenter study. Grouping the different markers to establish a prognostic scoring system may provide more accurate evaluation of the prognosis in OCSCC patients.